(3OjhGf GdCOH hejRGf GddZIs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s ((3MeRI Hf YHO GdYRjR GdebTQi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOkG jHdZ QVGg CeG HYO aEf Gddg JYGdi bOQ GdGTjGA HbOQJg aCeG GdReGf agh ReGf Cgd GdYde hGdHjGf hGdaUGMg s
(3BNQgG (B:s
(3hGSeCd Ci VeQ hCf dCe Gdbhe Ci GLJeYhG BNQ cJGH GdgeRI hgh cJGH OjhGf GdOH hejRGf GddZI s
(3GdfSNI HgG MhGTs
(3HChd agQSJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs